SPINAL K-WIRE MIGRATION FOLLOWING ACROMIOCLAVICULAR DISLOCATION SURGICAL TREATMENT: A CASE REPORT WITH SCOPING REVIEW DISCUSSION - Nizar Al Rhaazi; Ahmadin Y.R. Susatyo; Faesal; Yunus Abdul Bari (Majalah Biomorfologi, 2023)
Background: Kirschner wire as internal fixation is a common instrument used in any small bone, including on Acromioclavicular Dislocation Surgical Treatment (ADST). Due to the characteristic of the wire, which is less rigid than any other instrument, the wire can sometimes migrate unexpectedly into various locations. Wire migration has been reported sporadically since 1943. However, spinal migration is still underreported. In addition, the mechanism of spinal migration and the evacuation method remains unclear. Objective: The purpose of this study was to report a case of K-wire spinal migration to cervical vertebrae C6-C7 following surgical treatment and discuss the case using the results of a scoping review. Case: A 51 years-old man with wire migration to cervical vertebrae C6-C7 complained of painful sensations around the left side of the neck and left shoulder, which aggravated with shoulder movement. He underwent left acra omioclavicular joint repair surgery three years ago after a motorcycle accident. No other abnormalities were found in either physical or neurological examinations. Discussion: In the last 10 years, six cases of spinal migration after ADST have been reported, with less than one case reported a year. The cases' gender was all male, with a mean age of 43.33 years old. The majority of them underwent acromioclavicular fixation in 50% of cases, and the average time from migration to surgery is 71 months. The most common migration is located in the cervical region (66.67%), and the penetrating points are equal in all cases. In the non-bent wire group, an entire migration has been reported. The evacuation technique used in all previous cases was direct access surgery by gently pulling out the wire along its axis under visual control. Various mechanisms contribute to spinal migration, but shoulder movement is arguably the most influential factor. Conclusion: Cervical migration post-ADST commonly occurs and may cause severe morbidity.